A Theory of Channel Price Promotions - Gerstner, Eitan; Hess, James D. (American Economic Review, 1991)
Manufacturers can stimulate sales by a temporary wholesale price reduction for the retailer, a rebate directed toward consumers, or a combination of both. The trade-offs between these price promotions are analyzed, providing insights about their roles, profitability, and welfare properties. Retailers' rebates are also studied. While price discrimination is a common explanation for rebates to consumers, when a product is sold through a distribution channel, the manufacturer may also use rebates to motivate retail participation in the promotion. This explains why rebates may be offered even when all consumers use them and price discrimination does not occur. Copyright 1991 by American Economic Association.